Dampak Opinion Leadership terhadap Keinginan Penonton untuk Mengikuti Rekomendasi Produk dan Terus Menonton Konten (Studi pada Channel Youtube Review Produk Elektonik dan Gadget Ternama di Indonesia) - Sebastian Tjakradinata, Matthew; Ardianti, Retno (Jurnal Manajemen dan Organisasi, 2024)
This study was conducted to explain viewers’s intention to continue watching and to follow the recommendations given by opinion leaders on the YouTube platform. In addition, the effects of the characteristics of content such as originality, uniqueness and quality on opinion leadership. This study took a quantitative approach and relied on a survey data from viewers of the the most popular YouTube channels that specialized on electronic gadget review in Indonesia. By using Partial Least Square-Structural Equation Modeling (PLS-SEM) technique in data analysis, the results showed that there was a significant effect of perceived originality and perceived quality on opinion leadership. However, the effect of perceived uniqueness on opinion leadership was not significant. In addition, the findings showed that opinion leadership had positive and significant effects on viewers’ intention to follow the advice and to continue watching. In sum, the study higlights the importance of collaboration between business organizations and opinion leaders to create honest product reviews for viewers given its significant effects on the viewers’ consumption behavior.